Optimization of the Total Annual Cost in Heat Exchanger Networks with Multiple Utilities - Udochukwu, E.C; Ogbonnaya, B.U; Azeez, O.S (International Journal of Natural Sciences Research, 2021)
This research work was focused on optimizing heat exchanger network problems from literature involving multiple utilities with the objective function of minimizing the Total Annual Costs of the designed networks. This was achieved through the use of pinch methodology on Aspen Pinch software, Version 11.1. Supertargeting was used to obtain the minimum temperature difference for two case studies and the networks were designed on Grid Diagrams. The design of the networks was focused on the energy-capital costs tradeoffs, preventing the use of extra heat exchanger units to reduce energy costs at the expense of capital costs. This paid off as the networks designed in this research obtained the lowest total annual costs (TACs) when compared with the results obtained by other researchers on the case studies under review.